Global warming shifts the composition of the abundant bacterial phyllosphere microbiota as indicated by a cultivation-dependent and -independent study of the grassland phyllosphere of a long-term warming field experiment. Issue 8 (9th May 2020) - Aydogan, Ebru L; Budich, Olga; Hardt, Martin; Choi, Young Hae; Jansen-Willems, Anne B; Moser, Gerald; Müller, Christoph; Kämpfer, Peter; Glaeser, Stefanie P
ABSTRACT: The leaf-colonizing bacterial microbiota was studied in a long-term warming experiment on a permanent grassland, which had been continuously exposed to increased surface temperature (+2°C) for more than six years. Two abundant plant species, Arrhenatherum elatius and Galium album, were studied. Surface warming reduced stomata opening and changed leaf metabolite profiles. Leaf surface colonization and the concentration of leaf-associated bacterial cells were not affected. However, bacterial 16S ribosomal RNA (rRNA) gene amplicon Illumina sequencing showed significant temperature effects on the plant species-specific phyllosphere microbiota. Warming partially affected the concentrations of cultured bacteria and had a significant effect on the composition of most abundant cultured plant species-specific bacteria. The abundance of Sphingomonas was significantly reduced. Sphingomonas isolates from warmed plots represented different phylotypes, had different physiological traits and were better adapted to higher temperatures. Among Methylobacterium isolates, a novel phylotype with a specific mxaF type was cultured from plants of warmed plots while the most abundant phylotype cultured from control plots was strongly reduced. This study clearly showed a correlation of long-term surface warming with changes in the plant physiology and the development of a physiologically and genetically adapted phyllosphere microbiota. Abstract : Global warming shifts the phyllosphere microbiota.